College ethics - Esdon, Robert Alexander (My University, 1903)
Introduction: So great is the worth of human nature, so invaluable the human soul, that men have long striven to master the art of living. Their efforts have so educated the rational judgment that the mind of society is to-day ready to admit that the life’s work of every individual should result in the winning of some victory for humanity. To win victories there must be preparation. The various faculties of the body and of the mind must be trained. The influences of the home, the school, the church and the college must mold the character during the formative period. The college graduate should have comprehended the problems of his life’s occupation and be ready to enter into active service. Is it not reasonable then, in resenting the subject of college ethics to insist that a normal development of the student depends upon an opportunity, while he is comprehending the problems of his chosen occupation, also to comprehend the much greater problems concerning his relationship in life? If so, is the ethical atmosphere which surrounds our students such as to purify of contaminate those who enter it? Dwelling upon appearances we may be deceived by thinking that the conduct of the dominant faction within a limited square as of a college campus constitutes an index to the mind of its society. For often such conduct is due to wave of enthusiasm which sweep away the soundest judgments allowing the student to indulge, for a time, in acts that soon became universally offensive as being out of harmony even with the best judgment of the actors themselves. And yet, it is just these waves of enthusiasm that gave the student has first lessons in that which later may lead to the committing of acts criminal before the law. For example many times student bodies have assembled at appointed places, discussed for awhile some exciting subject and at the suggestion of some popular man, made a wild rush in mob-formation for to commit some rash act against the person or property of some, offensive or inoffensive person as the case may be.
Citation: Esdon, Robert Alexander. College ethics. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Boycot; Hazing; Linch-Law; Theses